The synthesis, mesomorphic and dielectric investigation of new unsymmetrical bent-core mesogens derived from 3-hydroxybenzoic acid - Ocak, Hale; Ozerol, Esma Ahlatcioglu; Celikel, Fulya Cagla; Okutan, Mustafa; Eran, Belkiz Bilgin (SPRINGER INT PUBL AG, 2020)
The synthesis, mesomorphic and dielectric investigation of new unsymmetrical bent-core mesogens derived from 3-hydroxybenzoic acid central core with linked two rodlike units carrying (S)-3,7-dimethyloctyloxy group and an n-alkyloxy chain at both terminals are presented. The liquid crystalline properties of the new unsymmetrical bent-core materials have been investigated by polarizing optical microscopy and differential scanning calorimetry. New compounds with the reversed ester linking unit exhibit a monotropic or enantiotropic columnar mesophase at lower temperatures as compared to analogs with a straight chain depending on the presence of the branched (S)-3,7-dimethyloctyloxy terminal chain. Dielectric measurements for one of the bent-core mesogens, 3-[[4-[[4-(octyloxy)benzoyl]oxy]benzoyl]oxy]benzoic acid 4-[[4-((S)-3,7-dimethyloctyloxy)phenoxy]carbonyl]phenyl ester (OBDPE), have been carried out on the angular frequency range from 25.12 to 50265k rad/s at different temperatures. Thanks to dielectric measurements, real and imaginary dielectric constant, conductivity mechanism and dielectric relaxation mechanism of OBDPE were obtained. [GRAPHICS] .
Keywords: Liquid crystals; Bent-core compounds; 3-Hydroxybenzoic acid derivatives; Columnar mesophase; Dielectric measurement; SHAPED LIQUID-CRYSTALS; CARBOXYL CONNECTING GROUPS; SMECTIC-A PHASE; HOMOLOGOUS SERIES; LATERAL SUBSTITUENTS; MESOPHASE BEHAVIOR; LINKAGE GROUPS; POLAR ORDER; TRANSITION; MOLECULES; Chemistry